2017
DOI: 10.1161/circheartfailure.117.003926
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Mortality Risk Scores and Postdischarge Events in Hospitalized Heart Failure Patients

Abstract: Background The Acute Decompensated Heart Failure National Registry (ADHERE) and Get with the Guidelines (GWTG) registries have developed simple heart failure (HF) in-hospital mortality risk scores. We hypothesized that HF scores predictive of in-hospital mortality would perform as well for early post-discharge mortality risk stratification. Methods and Results In this single center, community based, retrospective study of all consecutive primary HF hospitalizations (6203 hospitalizations in 3745 patients) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
2
24
0
3
Order By: Relevance
“…In addition to providing prognostic information, such models can play a crucial role in the management of certain patients, especially when outcomes are predicted to be poor and early palliative consult and/or hospice referral become more reasonable. Most of those prediction models shared similar variables, renal function, age, and blood pressure being the most studied variables [ 3 ]. However, these modules have been underutilized in the daily clinical practice due to their limited accuracy in predicting serious events [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing prognostic information, such models can play a crucial role in the management of certain patients, especially when outcomes are predicted to be poor and early palliative consult and/or hospice referral become more reasonable. Most of those prediction models shared similar variables, renal function, age, and blood pressure being the most studied variables [ 3 ]. However, these modules have been underutilized in the daily clinical practice due to their limited accuracy in predicting serious events [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over 60 risk scores have been previously developed to assess risks of adverse events in HF patients. 6,7) Among those risk scores, the following variables have emerged as the most consistent and strongest predictors: renal func- Values are expressed as median and interquartile range, or n (%). ACE-I indicates angiotensin-converting enzyme inhibitor; ALB, serum albumin; ARB, angiotensin-receptor blocker; BMI, body mass index; BNP, B-type natriuretic peptide; BUN, blood urea nitrogen; COPD, chronic obstructive pulmonary disease; Dd, diastolic dimension; Ds, systolic dimension; e', peak early diastolic velocity of the mitral annulus; EF, ejection fraction; eGFR, estimated glomerular filtration rate; Hb, hemoglobin; HbA1c, hemoglobin A1c; HF, heart failure; LAD, left atrial dimension; LV, left ventricular; MRA, mineralocorticoid receptor antagonist; and NYHA, New York Heart Association.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) Existing risk scores have focused mainly on long-term outcomes or inhospital mortality and were often complex and therefore, uniformly underutilized. [7][8][9] A recent study reported that the Acute Decompensated Heart Failure National Registry (ADHERE) Classification and Regression Tree (CART) algorithm and the Get With The Guidelines (GWTG) HF risk score, both of which were developed to predict in-hospital mortality, could also predict early post-discharge mortality. 7,8,10) However, models for the prediction of early post-discharge mortality in elderly HF patients are not well-established.…”
mentioning
confidence: 99%
“…Finally, multivariate analysis may mitigate bias after adjustment for pre-existing prognostic factors, which have been shown to stratify early post-discharge and long-term mortality risks. 18,33 However, unmeasured and unadjusted factors, such as pre-admission physical activity and other complications, including infection, paralysis, cognitive function, and physical disabilities, and changes in baseline variables, all of which may have an effect on gait speed, leave residual bias, and the results must be replicated in future studies.…”
Section: Study Limitationsmentioning
confidence: 99%